Blockchain Technologies as A Stimulator of Institutional Transformations of the World Financial System - Yuryevich Kussy, Mikhail; Viktorovna Pobirchenko, Viktoriya; Alekseevna Shutaieva, Elena; Yuryevich Kakutich, Yevgeny (International Journal of Engineering and Technology, 2018)
This paper briefly presents the recent problems of the world financial system. The analysis of indicators of blockchain technologies has been carried out; their attractive aspects and disadvantages are singled out. Some potential possibilities of using blockchain technologies in various fields of activity are considered. Particular attention is paid to the prospects of application of blockchain technologies in the world financial system, which will allow solving a number of problems of the world financial system itself. The issues (including those of regulatory and institutional nature and predictable social strain as well) that people can face when implementing blockchain technologies in their everyday life, have been noted. The institutional changes in the world financial system that could appear after implementation of blockchain technologies are highlighted.Â Â